若a+b+c=0,且(b-c)÷a+(c-a)÷b+(a-b)÷c=0,则(bc+b-c)÷b^2c^2+(ca+a-c)÷c^2a^2+(ab+a-b)÷a^2b^2=

来源:百度知道 编辑:UC知道 时间:2024/05/15 01:17:35

若a+b+c=0,且(b-c)/a+(c-a)/b+(a-b)/c=0,求(bc+b-c)/b²c²+(ca+c-a)/c²a²+(ab+a-b)/a²b²的值。

解:将(b-c)/a+(c-a)/b+(a-b)/c=0去分母,并整理,得:
b²c-c²b+c²a-a²c+a²b-b²a=0
a²b-a²c+b²c-b²a+c²a-c²b=0
所以:将欲求式子通分,得:
(bc+b-c)/b²c²+(ca+c-a)/c²a²+(ab+a-b)/a²b²
=[a²(bc+b-c)+b²(ca+c-a)+c²(ab+a-b)]/a²b²c²
=[(a²bc+b²ca+c²ab)+(a²b-a²c+b²c-b²a+c²a-c²b)/a²b²c²
=[abc(a+b+c)+(a²b-a²c+b²c-b²a+c²a-c²b)]/a²b²c²
=(a²b-a²c+b²c-b²a+c²a-c²b)/a²b²c²
=0